Idosos conectados: a interação da terceira idade com as redes sociais digitais no interior do Rio Grande do Norte - Borges, Aldeci Allyson Pereira (Universidade Federal Rural do Semi-Árido, 2019)
Currently, social networks are targeted to the public and have a large share of users worldwide, including the years, who have a growth for people who use these tools. The problem is that group interaction with social networks is still little explored. In this, this study aims to investigate how the elderly in the interior of Rio Grande do Norte interact with digital social networks in their daily lives. For the methodology, the focal group was used as a data collection tool, being applied to the target public in the city of Angicos, in the interior of Rio Grande do Norte. Then, the entire debate was transcribed and processed in Iramuteq software, which, together with the use of the proposal proposed by Bardin (2002), assisted in the analysis of the data. The results allowed that, as the digital information systems most used by the elderly are Facebook and Facebook, being motivated by curiosity and the need to stay connected with family and friends. However, it has also been revealed that the elderly are very concerned about the issue of safety and exposure, which limits the use of group resources.
Monografia
Keywords: Idosos; Redes sociais digitais; Tecnologias da informação e comunicação; Seniors; Digital social networks; Information and communication technologies; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::SISTEMAS DE INFORMACAO